Ihtikar 's Behavior Towards Rising Price and Rarity of Fried Oil Tree Materials: A Study of Takhrij and Syarah Hadith - Zuadah, Annisaa Siti; Abdurrahman, Muhammad Fadhil (Journal of Takhrij Al-Hadith, 2024)
This study aims to discuss the behavior of ihtikar towards rising prices and scarcity of oil staples. This research uses a qualitative approach, by applying descriptive-analysis methods. The formal object of this research is the science of hadith, while the material object is the hadith about the behavior of ihtikar (hoarding) in the narration of Abu Dawud No. 2990. The results and discussion of this study show that the status of hadith about ihtikar quality shahih, which meets the qualifications of maqbul ma'mul bih for Islamic practice and can be used as signposts (introspection) in avoiding behavior that does not reflect Islamic morals, namely carrying out buying and selling activities that lead to tyranny which results in harming many people and the perpetrators are reproached by Shara'.